Transition to Knowledge Society in Turkey: Current State and Future Perspectives - YILMAZ, YÜCEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2012)
The purposes of this study are to evaluate the phase Turkey is in with regard to the transition to a knowledge society and to discuss the priorities in relation to this process in the future. In this task, first, the concept of knowledge society is examined according to various views along with the properties that such a sociological structure needs to have. Then, the current state of Turkey is assessed. This is carried out on the basis of different studies published by International Telecommunication Union, United Nations, and Turkish State Planning Organization. In the last section, it is discussed how the transition process to a knowledge society in Turkey can be managed in a more effective and efficient way. This study points out that in Turkey important improvements especially with regard to infrastructure and education have to be achieved.